A tale of two unusual anaerobic bacterial infections in an immunocompetent man: A case report and literature review. (October 2021) - Chesdachai, Supavit; Eberly, Allison R.; Razonable, Raymund R.
Abstract: We report a case of an immunocompetent man who presented with Desulfovibrio fairfieldensis bacteremia, followed by an epidural abscess due to Parvimonas micra . Only few cases have described unique clinical features related to both organisms, and this report illustrates two distinct sequential, if not concurrent, syndromes due to these anaerobes. Highlights: D. fairfieldensis and P. micra are anaerobic members of the human microbiota. Human infections due to D. fairfieldensis and P. micra are rarely reported. Most cases of D. fairfieldensis bacteremia were transient. P. micra is a rare causative agent for an epidural abscess. The source of both infections is most often the gastrointestinal tract.